Physiological closed-loop control in intelligent oxygen therapy: A review. (July 2017) - Sanchez-Morillo, Daniel; Olaby, Osama; Fernandez-Granero, Miguel Angel; Leon-Jimenez, Antonio
Highlights: Studies, trials and researches published in the context of automated close-loop oxygen administration systems in adults are retrospectively reviewed. When compared to the conventional oxygen therapy devices, the closed-loop controllers maintain higher saturation levels, spend less time below the target saturation, and save O2 resources. Closed-loop controlled oxygen therapy devices are scarce in real clinical applications. Main barriers such as robustness of control algorithms, fail-safe mechanisms, limited reliability of sensors, usability issues and the need for standardized evaluating methods of assessing risks are discussed. This study provides recommendations for future related interventions, in order to promote the wide spreading of a new generation of oxygen devices. Abstract: Background and Objective: Oxygen therapy has become a standard care for the treatment of patients with chronic obstructive pulmonary disease and other hypoxemic chronic lung diseases. In current systems, manually continuous adjustment of O2 flow rate is a time-consuming task, often unsuccessful, that requires experienced staff. The primary aim of this systematic review is to collate and report on the principles, algorithms and accuracy of autonomous physiological close-loop controlled oxygen devices as well to present recommendations for future research and studies in this area. Methods: A literature search was performed on medical database MEDLINE, engineering database IEEE-Xplore and wide-raging scientific databases Scopus and Web of Science. A narrative synthesis of the results was carried out. Results: A summary of the findings of this review suggests that when compared to the conventional manual practice, the closed-loop controllers maintain higher saturation levels, spend less time below the target saturation, and save oxygen resources. Nonetheless, despite of their potential, autonomous oxygen therapy devices are scarce in real clinical applications. Conclusions: Robustness of control algorithms, fail-safe mechanisms, limited reliability of sensors, usability issues and the need for standardized evaluating methods of assessing risks can be among the reasons for this lack of matureness and need to be addressed before the wide spreading of a new generation of automatic oxygen devices.